The Marriage of Mathematics and Programming - Ferreira, Bernardo M.; Souza, Lucas M.; Silva, Laira A.; Félix, Igor M.; Brandão, Leônidas O.; Brandão, Anarosa A. F. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na Educação, 2019)
In a world where computing skills are a must-have, programming is still a hard one to acquire and its courses have high failure rates. Numerous studies propose ways to help the early identification of students that might face difficulties and are more likely to fail a programming course. This study aims to find a correlation between their mathematical abilities and grades in an introductory computer science class following the method of a previous study that had promising results. Students were asked to answer a mathematical abilities test and had their results compared to their grades during the course using the Wilcoxon-Mann-Whitney non-parametric test. The results indicate a strong correlation between mathematical abilities and programming potential.